Analysis of Phenotypic Variables and Differentiation Between Untypical Crohn’s Disease and Untypical Intestinal Tuberculosis - Meng, Yu; Li, Ying; Hao, Rong; Li, Xiaojun; Lu, Fanggen (Digestive diseases and sciences, 2019)
Background The differentiation between untypical intestinal tuberculosis (UITB) and untypical Crohn’s disease (UCD) is a challenge. Aims To analyze phenotypic variables and propose a novel prediction model for differential diagnosis of two conditions. Methods A total of 192 patients were prospectively enrolled. The clinical, laboratory, endoscopic, and radiological features were investigated and subjected to univariable and multivariable analyses. The final prediction model for differentiation between UCD and UITB was developed by logistic regression analysis and Fisher discriminant analysis on the training set. The same discriminant function was tested on the validation set. Results Twenty-five candidates were selected from 52 phenotypic variables of typical Crohn’s disease (TCD), UCD, and UITB patients. UCD’s variables overlapped with both TCD and UITB. The percentages of tuberculosis history, positive PPD, and positive T-SPOT result in UCD were all significantly higher than that in TCD (11.6% vs. 0.0%, 27.9% vs. 0.0%, 25.6% vs. 4.5%, respectively, P < 0.05). The regression equations and Fisher discriminant function for discrimination between UCD and UITB were developed. In the training data, the area under the receiver operating characteristic of equations was 0.834, 0.69, and 0.648 in the clinical-laboratory, endoscopic, and radiological model, respectively. The accuracy of Fisher discriminant function for discrimination was 86% in UCD and 73% in UITB in the validation data. Conclusions Phenotypes of UCD patients in TB-endemic countries may be associated with TB infection history. Fisher discriminant analysis is a good choice to differentiate UCD from UITB, which is worthy of verification in clinical practice.